The role of small-scale and community-based projects in future development of the marine energy sector - Proimakis, Nikolaos; Tara, Hooper; Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2021)
Despite high expectations for the sector, most marine energy technologies remain in the research and development, or at best demonstration, phase. The industry is in a period of stagnation, and requires new approaches to overcome the challenges that inhibit widespread deployment. Small-scale initiatives have proven to be a successful means of developing other renewable technologies but their role in supporting marine energy is not well researched. This paper provides a review of the barriers and opportunities presented by different policy landscapes, financial support mechanisms, markets, key actors, and wider regulatory and governance issues. Semi-structured interviews with marine energy stakeholders from the UK, Canada and Denmark were used to explore the role of small-scale marine energy projects, and were supplemented by interviews with the general public in England. This showed that while marine energy is appropriately scalable for local projects, financing remains a major hurdle. Discretionary local authority finance, as well as other novel options such as crowdfunding, tends to be relatively modest, supporting the argument for small-scale projects. A market for smaller devices exists, particularly for remote communities currently dependent on expensive energy from oil-fired generators. There remains a significant role for small-scale projects in testing the technology, contributing to reductions in cost and environmental risk. Current processes for environmental impact assessment can present a significant hurdle for small projects, but proportionate, adaptive assessments are evolving. Finally, community ownership and public participation have the potential to increase advocacy for the industry, with multi-actor partnerships presenting a positive way forward.